The Evolution of Pedagogical Terminology: Historical Development and Practical Implications - Malohat Odilova (Indonesian Journal Publisher, 2025)
The formation and development of pedagogical terminology reflect the evolution of educational thought and the changing nature of teaching and learning across historical epochs. This article investigates the historical trajectory of pedagogical terms, focusing on how they emerged, transformed, and became institutionalized in educational discourse. By reviewing significant milestones in pedagogy, from classical antiquity to the digital age, and exploring how pedagogical terms were coined and adapted, the study demonstrates how terminology influences and is influenced by pedagogical practices. The article includes a literature review, critical analysis, and discussion of implications for contemporary education